Aggressiveness of care at end of life in patients with high‐grade glioma. (9th November 2021) - Harrison, Rebecca A.; Ou, Alexander; Naqvi, Syed M. A. A.; Naqvi, Syed M.; Weathers, Shiao‐Pei S.; O'Brien, Barbara J.; de Groot, John F.; Bruera, Eduardo
Abstract: Background: Patients with high‐grade glioma (HGG) face unique challenges toward the end of life (EoL), given their aggressive trajectory and neurologic deterioration. Aggressiveness of medical care at EoL has been identified as an important quality metric for oncology patients. At this time, limited data exist around the nature of EoL care of patients with HGG. Methods: Patients with HGG and palliative care (PC) referral seen between 2010 and 2015 were identified ( N = 80). Of these, N = 52 met inclusion criteria. Random selections of patients with (1) HGG not referred to PC ( n = 80), and (2) non‐CNS cancers with PC referral ( n = 80) were identified for comparison. A composite score of aggressiveness of medical care at EoL was calculated for each patient from predetermined variables. A time of eligibility for PC was defined for each patient when predetermined criteria based on symptom burden, functional status, and prognosis were met. Results: Among the patients analyzed with HGG referred to PC, 59.6% ( N = 31) were referred as inpatients, and 53.8% ( N = 28) were referred within the last 12 weeks of life. Patients with HGG had similar aggressiveness of care at EoL regardless of PC referral, and HGG patients had less aggressive care at EoL than patients with non‐CNS cancers ( p = 0.007). Care was more aggressive at EoL in HGG patients who received late versus early PC referrals ( p = 0.012). Motor weakness at time of eligibility (OR = 2.55, p = 0.002) and more disease progressions (OR = 1.25, p = 0.043) were associated with less aggressive care at EoL. Conclusions: Early clinical‐ and disease‐related features predict the aggressiveness of medical care at EoL in patients with HGG. Formal PC consultation is used infrequently and suboptimally in patients with HGG. Our data suggest that the role of PC in improving EoL outcomes in HGG warrants further evaluation. Abstract : Aggressiveness of medical care at end of life (EoL) has been identified as an important quality metric for EoL care; however, to date, this has not been studied in patients with high‐grade glioma. This retrospective study finds less aggressive medical care at EoL in patients with glioma compared with other cancers. We also found that palliative care is often used late and in the inpatient setting in this population, limiting its clinical impact.